'But we are different!' : 12 Common Weaknesses in Banking Laws, and What to Do About Them - Bossu, Wouter (IMF Working Papers; Working Paper, 2015)
Well-designed banking laws are critical for regulating the market access and operations of banks, as well as their removal from the market in case of failure. While at a financial policy level there is a broad consensus as to the content of banking laws, from a legal perspective their drafting often leaves something to be desired. In spite of what is often argued, the types of weaknesses of banking laws are hardly country-specific; many weaknesses are shared by many banking laws. This working paper discusses those weaknesses and ways to remedy them, by focusing on a selected set of legal policy principles.